Prevalence of Dental Caries in Kosovar Adult Population. (19th July 2016) - Kamberi, Blerim; Koçani, Ferit; Begzati, Agim; Kelmendi, Jeta; Ilijazi, Donika; Berisha, Nora; Kqiku, Lumnije
Abstract : Objectives . The aim of this study was to assess the prevalence of dental caries in the Kosovar adult population. Materials and Methods . A cross-sectional study in Kosovo was conducted examining 9387 patients, aged 18 upwards, between January 2010 and December 2011. Clinical evaluation was done using WHO criteria for evaluation of dental health status and data collection. Results . The prevalence of caries for the whole study was 72.80%. The mean DMFT index was 9.61 (±5.12) in the 18–34-year age group, 11.6 (±6.42) in the 35–44-year age group, 13.68 (±8.12) among the 45–64-year age group, 17.98 (±9.81) in the 65–74-year age group, and 23.19 (±9.41) in the age group of 75+ years, respectively. A significant difference of mean DMFT and its each component was observed between the ages (P < 0.001 ). Conclusion . This study comes out with the significant levels of dental caries among young Kosovar population (18–34 years old).